THE INFLUENCE OF AUDIT COMMITTEE QUALITY, BOARD OF COMMISSIONER’S QUALITY, INSTITUTIONAL OWNERSHIPS, MANAGEMENT OWNERSHIPS TOWARD EARNINGS MANAGEMENT PRACTICE AND FINANCIAL PERFORMANCE AND THE IMPLICATION TOWARD THE FIRM VALUE (Survey on The Go-Public Companies Listed in The Indonesian Stock Exchange) - Harnovinsah Harnovinsah (AKUNTABILITAS, 2012)
Financial report is an important factor for inventors to make investment decisionin capital market. The. Publicity of financial report which has relevant information fordecision making will be reacted by market player. Many investors and other users offinancial report do not pay attention to the process of publishing financial report, so itpushes the emergence of dysfunctional behaviours, like earnings managementpractices.The purpose of this research is to study and to find out empirically theresearch’s evidence about the influence of audit committee and board of commissioner’squality, institution and management ownerships toward earnings management practiceand financial performance and their implication toward firm value. The population of thisresearch is companies listed in Indonesian Stock Exchenge during the period 2007 – 2010in amount of 105 companies. Based on the criteria, there are only 60 companies chosen assample.The Method of analysis used in this research is path analysis, with the followinghypotheses: (1) The Audit committee and the board of commissioner’s quality, institutionand management ownership have influence on the earnings management practice. (2) TheAudit committee and the board of commissioner’s quality, institution and managementownership, the earnings management practice have influence on corporate financialperformance. (3) The earnings management practice and corporate financial performancehave influence on firm value.The results of this study indicate (1)The audit committeequality negatively influence on earnings management practice, (2) The board ofcommissioner’s quality negatively influence on earnings management practice (3) Theinstitutional ownership negatively influence on earnings management practice (4) themanagerial ownership negatively influence on earnings management practice but notsignificantly (5) simultaneously The audit committee quality, The board ofcommissioner’s quality, institutional ownership and managerial ownership, havesignificant influence on earnings management practice, and (6) earnings managementpractice positively influence on corporate financial performance but not significant, (7)earnings management practice positively influence on firm value, but not significant, (8)corporate financial performance positively influence on firm value.